Simulation Analysis and Experimental Research on Vacuum Freeze-drying of Pitaya - Zhang Tong; Yu Kezhi; Zhang Dezheng (Zhileng xuebao)
To accurately forecast freeze-drying time, COMSOL software was used to simulate the sublimation drying process of pitaya slices based on the theory of heat and mass transfer in this study. The thickness of the red pitaya slices was 12 mm, and the radius was 4 cm. By simulating the water vapor flow coupled with the heat and mass transfer of the sublimation drying stage, the temperature distribution characteristics of pitaya slices, the movement of the sublimation interface, and the condition of ice sublimation, the sublimation cycle was forecast. Experiments were conducted to validate the model. The results show that the errors are low: the absolute error between the simulated and measured pitaya center temperatures is 0.9 ℃, the comparative error between the forecast and measured moisture ratios is only 1.2%, and the relative error between the simulated and measured dehydration rates is 6.63%. It can be concluded that the model can accurately simulate the dynamic changes in heat and mass transfer during the sublimation drying process. By comparing the simulated sublimation cycle of pitaya slices with different thicknesses, and considering the quality and production of freeze-drying products, it is concluded that 12 mm is the best thickness of red pitaya slices for freeze-drying.